Pengaruh Ethical Sensitivity dan Love of Money Terhadap Persepsi Mahasiswa Akuntansi Mengenai Perilaku Tidak Etis Akuntan : Analisis Multigrup Gender - Verawati, Ona; Affandy, Didied Poernawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study proposes to examine the effect of ethical sensitivity and love of money on accounting students’ perceptions of accountants’ unethical behaviour with gender as the moderating variable, involving the accounting department students of Universitas Brawijaya, Malang, class of 2018 and 2019, as the research object. This study employs the quantitative approach utilizing data collected from questionnaires and includes 100 respondents selected through non-probability sampling. The result of the data analysis utilizing Partial Least Square (PLS) using SmartPLS version 3.2.9 exhibited that ethical sensitivity had a positive effect on accounting students’ perceptions of accountants’ unethical behaviour, and love of money had a negative effect on accounting students’ perceptions of accountants’ unethical behaviour. In addition, gender did not moderate the relationship between ethical sensitivity and love of money on accounting students’ perceptions of accountants’ unethical behaviour. Abstrak Penelitian ini bertujuan untuk menguji pengaruh ethical sensitivity dan love of money terhadap persepsi mahasiswa akuntansi mengenai perilaku tidak etis akuntan dengan gender sebagai variabel moderasi. Objek penelitian ini adalah mahasiswa angkatan 2018 dan 2019 jurusan akuntansi Universitas Brawijaya Kota Malang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode kuesioner dengan teknik sampel non-probability sampling dengan total 100 responden. Analisis dilakukan menggunakan Partial Least Square (PLS) dengan bantuan software SmartPLS versi 3.2.9. Hasil penelitian ini menunjukkan bahwa ethical sensitivity berpengaruh positif terhadap persepsi mahasiswa akuntansi mengenai perilaku tidak etis akuntan dan love of money berpengaruh negatif terhadap persepsi mahasiswa akuntansi mengenai perilaku tidak etis akuntan. Selain itu, gender tidak dapat memoderasi pengaruh ethical sensitivity dan love of money terhadap persepsi mahasiswa akuntansi mengenai perilaku tidak etis akuntan.